Economia doméstica: uma disciplina escolar no secundário ginasial sergipano do Atheneu Sergipense (1944-1954) - Almeida, Sayonara do Espirito Santo (2016)
The present research aims at examining, through the genesis, function and functioning, the school discipline Home Economics in the junior high school of the College Atheneu Sergipense (1944 to 1954). Discipline absent from today's school curriculum, Home Economics was inserted in Brazilian education from Decree-Law 4,244 of April 9, 1942 and whose target audience was only girls who should, from an early age, learn to run a house according to changes taking place in the period. I use for this analysis the concepts of curriculum (GOODSON, 1997; 2001) and school discipline (CHERVEL, 1990). Because it is a female school subject, the approach used is also part of the theoretical field of Women's History, as defined by Priore (2012). Based on Documentary and historiographic features, the sources that support this writing correspond to: laws, newspapers, classbooks, correspondence, log book, written tests cataloged in the Center of Education and Memory of Atheneu Sergipense (CEMAS) and in the Historical and Geographical Institute of Sergipe (IHGSE).In possession of the documents and records made from readings referring to the researched subject, this study was carried out. Beyond providing knowledge aimed at the formation of good mothers, wives and housewives, the teaching of Home Economics enabled scientific and hygienic notions that supported the development of other trades.